American ginseng modulates pancreatic beta cell activities - Luo Luguang; Luo John; Wu Zonggui (BMC, 2007)
Abstract The mechanism of the beneficial effects of Panax quinquefolius (Xiyangshen, American ginseng) on diabetes is yet to be elucidated. Recent studies show that Panax quinquefolius increases insulin production and reduces the death of pancreatic beta cells. Mechanism studies indicate that Panax quinquefolius improves cell's immuno-reactivity and mitochondrial function through various factors. Clinical studies show that Panax quinquefolius improves postprandial glycemia in type 2 diabetic patients. Further studies to identify the component(s) of Panax quinquefolius linked with pancreatic islets/beta cells in vitro and in vivo are warranted for better understanding of the full effects of Panax quinquefolius.